2016
DOI: 10.7120/09627286.25.1.055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carprofen, meloxicam and butorphanol on broiler chickens’ performance in mobility tests

Abstract: (Gait Score (GS) 2.5-4) and non-lame (GS 0-1) broilers administered analgesia or a saline control.We used exploratory subcutaneous doses of the Non-Steroidal Anti-Inflammatory Drugs meloxicam (5mg/ kg) or carprofen (35mg/kg) or the opioid butorphanol tartrate (4mg/kg). We included butorphanol to explore the possibility that NSAID drugs could improve mobility by reducing inflammation without necessarily invoking an analgesic effect. Lameness was a significant predictor in all analyses. Neither the number of obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In another scenario, leg muscles may remain unaffected while gait of clinically normal looking birds is affected by subtle sickness behavior, mediated by for example pain in breast muscles or elsewhere. It has previously been suggested that lameness in broiler associates with pain (Hothersall et al, 2016). Wooden breast myopathy manifests in larger breast muscles (Kuttappan et al, 2017) making it difficult to tease apart the effects of body weight, age and wooden breast myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In another scenario, leg muscles may remain unaffected while gait of clinically normal looking birds is affected by subtle sickness behavior, mediated by for example pain in breast muscles or elsewhere. It has previously been suggested that lameness in broiler associates with pain (Hothersall et al, 2016). Wooden breast myopathy manifests in larger breast muscles (Kuttappan et al, 2017) making it difficult to tease apart the effects of body weight, age and wooden breast myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Potential links between GS and different aspects of broiler welfare have been studied. However, most experiments have compared lame broilers (GS ≥ 3) with broilers assessed as GS0 (e.g., McGeown et al., 1999 ; Hothersall et al., 2016 ; Aydin, 2017 ) and thus often excluded birds of GS1 and GS2 as being intermediate scores. As an exception, Skinner-Noble and Teeter (2009) compared different aspects of the welfare of broilers assessed as GS2 vs. GS3, but to our knowledge, no studies have examined and compared characteristics of birds specifically with GS0–GS2.…”
Section: Introductionmentioning
confidence: 99%
“…In a test of locomotor ability, broilers assessed as GS3 took longer to transverse an obstacle course compared to GS0 broilers, but this difference disappeared if the lame birds were administered carprofen, a nonsteroidal anti-inflammatory drug ( NSAID ) ( McGeown et al., 1999 ). Furthermore, another study comparing broilers assessed as GS2–GS4 vs. GS0–GS1 found that the former group showed decreased latency to lie in a motivational test and that administration of NSAIDs (carprofen and meloxicam) increased this latency ( Hothersall et al., 2016 ). These results suggest that pain can be a factor in the impaired walking ability: impaired birds experienced pain relief from the drugs, which improved their performance in the mobility tests.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired walking ability, varying from slight changes in gait to obvious lameness or even lack of mobility, is common in broiler production 1 , 2 . Typically, the majority of the impacted birds have a slight or definite defect, categorised as gait scores (GS) 1 and 2, 3 5 but research has mainly focused on the causes and welfare consequences of GS ≥ 3 6 9 …”
Section: Introductionmentioning
confidence: 99%